PENCATATAN KELAHIRAN ONLINE : MODEL PELAYANAN DALAM RANGKA MEWUJUDKAN GOOD GOVERNANCE - Mansari, Mansari Mansari; Mahmuddin, Mahmuddin Mahmuddin; Rizkal, Rizkal Rizkal (Universitas Islam Negery Ar-raniry, 2018)
The Population and Civil Registration Service of Banda Aceh city continues to make various efforts in providing population administration services to the community. One of the innovations that developed was online birth registration, where the community utilizes modern technology. The recording model has become stimulation for other regions in Aceh who want to apply the same thing. Even, there were other areas that have learned good practices that had been implemented in Banda Aceh. This study aims to determine the background that led to the initiation of online birth registration and the impact of online birth registration on the expansion of birth ownership. The research method used was qualitative research and the data were analyzed descriptively. Data were obtained through in-depth interviews with relevant stakeholders. The results showed that the background that led to the creation of online birth certificates were: to utilize modern technology; to facilitate the community; to implement the inspiration that came when was doing a comparative study to Pasuruan with the Education and Community Study Center (PKPM) team; and the presence of community that had no time to conduct the birth certificate . The existence of online birth registration has a very big impact on the community, which increasing the scope of birth certificates and speeding up the management process which can be handle at any time and at any moment.